Respuesta :
a.
A = 400 (1 + (0.02)/4)^4t where t = number of years and A = amount after t years
simplifying that becomes
A = 400 (1.005)^4t
b amount after 5 years is
400 (1.005)^(4*5) = 400 (1.005)^20 = $ 441.96
A = 400 (1 + (0.02)/4)^4t where t = number of years and A = amount after t years
simplifying that becomes
A = 400 (1.005)^4t
b amount after 5 years is
400 (1.005)^(4*5) = 400 (1.005)^20 = $ 441.96
a.
A = 400 (1 + (0.02)/4)^4t where t = number of years and A = amount after t years
simplifying that becomes
A = 400 (1.005)^4t
b amount after 5 years is
400 (1.005)^(4*5) = 400 (1.005)^20 = $ 441.96
Read more on Brainly.com - https://brainly.com/question/4656068#readmore